Elite wheelchair rugby: a quantitative analysis of chair configuration in Australia. Issue 3 (September 2016) - Haydon, David; Pinder, Ross; Grimshaw, Paul; Robertson, William
Abstract Limited recommendations of wheelchair configurations for court sports have been identified in the published literature. To accommodate the wide range of impairments in wheelchair rugby, players are given a point score that reflects their impairment. Players have regularly been grouped as high-, mid-, or low-point players in research, with high-point players having greater levels of muscle function compared with other classifications. This research documented the wheelchair configurations of elite Australian wheelchair rugby players across classification groups. Significant differences (p  < 0.05) were found for increased seat height and decreased seat depth for high-point players compared with low- and mid-point groups, respectively. Low-point players displayed reduced wheelchair mass compared with high- and mid-point players, as well as increased frame length. Camber angles showed no significant differences across the classification groups. The incorporation of anthropometric measures, such as the elbow angle at the top dead center, was also investigated. While elbow angle showed no significant differences, seat height-to-total arm length ratio was higher for high-point players. Participants also completed surveys detailing their perception of the effect of altering wheelchair configurations. It is suggested that wheelchair configurations should consider an individual's anthropometrics, impairment, training history, and court role to promote optimal performance, with predictive modeling having the potential to reduce the associated time and cost.